2018
DOI: 10.3390/su10103474
|View full text |Cite
|
Sign up to set email alerts
|

Positive Secular Trend in Slovak Population Urges on Updates of Functional Dimensions of Furniture

Abstract: The presented study is focused on the evaluation of the changes in weight and height of the adult population in Slovakia to provide updated information on the secular growth trend. The main objective was to identify and quantify the pace of gradual changes in the dimensions of the Slovak adult population, which is key ergonomic information for multiple disciplines. The measurements of weights, heights and body mass indices of the current adult population of Slovakia ranging from 26 to 94 years of age that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…In Slovakia, the effect of body weight on the size of chair joints was analysed in the study [46]. At the same time, the effect of a secular trend on functional dimensions of furniture was studied [47]. Czech authors [48] dealt with the use of anthropometric data in connection with seating and bed furniture as well.…”
Section: Introductionmentioning
confidence: 99%
“…In Slovakia, the effect of body weight on the size of chair joints was analysed in the study [46]. At the same time, the effect of a secular trend on functional dimensions of furniture was studied [47]. Czech authors [48] dealt with the use of anthropometric data in connection with seating and bed furniture as well.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Lee and Cha [50] report that console operators in nuclear power plants face human-computer interaction problems due to inappropriate console design; consequently, they redesigned the consoles by considering anthropometry. In conclusion, based on the previous examples, the correct use of anthropometry in workstation redesign improves the well-being, health, comfort, and safety of operators [51].…”
Section: Sustainability Emphasis In Project Portfolio Managementmentioning
confidence: 66%
“…If only the period covered by this study is observed (from 1979 to 1987), changes in body height are not visible, which is logical, because a nine-year period is too short for a noticeable secular trend (Hitka et al, 2018;Lopuszanska-Dawid et al). Furthermore, it is interesting to compare the average body weight and body mass index of respondents from this study (measured from 1979 to 1987), whose value is 66.62±8.35 kg for body weight and 21.55±2.29 kg/m 2 for body mass index, with respondents measured by Gardasevic et al (2015), also on a sample of Montenegrin adolescents.…”
Section: Resultsmentioning
confidence: 97%